2020
DOI: 10.1039/d0dt01380c
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Cu(i) P-type ATPase pumps are electrogenic uniporters

Abstract: Real-time transport analyses define transmembrane Cu(i)-pumps as electrogenic uniporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…It was concluded that the electrogenicity of ATP8A2 is related to a step in the ATPase transport cycle directly involved in translocation of the phospholipid [ 32 ]: dephosphorylation of the E 2 P intermediate, activated by lipid binding from the exoplasmic side, and/or the subsequent E 2 → E 1 conformational transition of the dephosphoenzyme, which is associated with release of the lipid to the cytoplasmic side [ 104 ]. It is noteworthy that the findings of the SSM study of the mammalian phospholipid flippase [ 32 ] support the view that the P4-ATPase is most likely an electrogenic uniporter, as also recently reported for a bacterial Cu + -transporting P1B-ATPase [ 82 ].…”
Section: P-type Atpases Investigated On Solid Supported Membranessupporting
confidence: 61%
See 1 more Smart Citation
“…It was concluded that the electrogenicity of ATP8A2 is related to a step in the ATPase transport cycle directly involved in translocation of the phospholipid [ 32 ]: dephosphorylation of the E 2 P intermediate, activated by lipid binding from the exoplasmic side, and/or the subsequent E 2 → E 1 conformational transition of the dephosphoenzyme, which is associated with release of the lipid to the cytoplasmic side [ 104 ]. It is noteworthy that the findings of the SSM study of the mammalian phospholipid flippase [ 32 ] support the view that the P4-ATPase is most likely an electrogenic uniporter, as also recently reported for a bacterial Cu + -transporting P1B-ATPase [ 82 ].…”
Section: P-type Atpases Investigated On Solid Supported Membranessupporting
confidence: 61%
“…Thus, SSM measurements on ATP7A/B supported the hypothesis that Cu + release in these enzymes may not be coupled to a net proton countertransport, which has not been observed for PIB-type ATPases [ 72 , 73 , 81 ]. Interestingly, a very recent study reported real-time fluorescence measurements on E.coli Cu + -ATPase (EcCopA) reconstituted in small unilamellar vesicles encapsulating a set of fluorescence probes that are selective for Cu + , pH, and membrane potential [ 82 ]. The results of this study demonstrated the absence of H + countertransport in the Cu + translocation cycle of EcCopA, qualifying EcCopA as an electrogenic uniporter.…”
Section: P-type Atpases Investigated On Solid Supported Membranesmentioning
confidence: 99%
“…Cu transport by CopA-like P 1B -type ATPases has been extensively studied using different methods ( Gonzalez-Guerrero et al, 2010 ; Völlmecke et al, 2012 ; Drees et al, 2015 ; Abeyrathna et al, 2020 ; Tadini-Buoninsegni, 2020 ), but similar information on CcoI-type ATPases is limited. Cu transport by CopA1 and CopA2 of Pseudomonas aeruginosa has been determined by using E. coli expressed proteins and monitoring 64 Cu accumulation in membrane vesicles ( Gonzalez-Guerrero et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…45,46 These catalytically driven pumps constitute an essential system to drive the selective translocation and export of Cu + ions, thereby controlling the intracellular Cu + levels. 47,48 Their activity tightly balances the biogenesis and integrity of copper centers in vital enzymes to non-toxic intracellular copper levels. The CopA structure is characterized by the existence of an 8 TM helices membrane domain (M-domain) connected to large cytosolic domains (N-, P-and A-domains) responsible for ATP hydrolysis, phosphorylation and energy transduction, allowing Cu + translocation across the membrane.…”
Section: Stabilization Of Purified Transmembrane Proteinsmentioning
confidence: 99%
“…The CopA structure is characterized by the existence of an 8 TM helices membrane domain (M-domain) connected to large cytosolic domains (N-, P-and A-domains) responsible for ATP hydrolysis, phosphorylation and energy transduction, allowing Cu + translocation across the membrane. 35,45,47,49 As a result of their critical involvement in essential iron and copper metabolism, both IroT and CopA homologues have been identified as key virulence factors in bacterial pathogens. 37,50 Transmembrane proteins, including IroT and CopA, are commonly extracted from membranes and purified as detergent micellar complexes for solubilization in aqueous environments.…”
Section: Stabilization Of Purified Transmembrane Proteinsmentioning
confidence: 99%